Association of low body surface area with dose reduction and/or discontinuation of nintedanib in patients with idiopathic pulmonary fibrosis: a pilot study: BSA and nintedanib reduction/discontinuation - Toi, Yukihiro; Kimura, Yuichiro; Domeki, Yutaka; Kawana, Sachiko; Aiba, Tomoiki; Ono, Hirotaka; Asou, Mari; Tsurumi, Kyoji; Suzuki, Kana; Shimizu, Hisashi; Sugisaka, Jun; Saito, Ryohei; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: We have often encountered adverse events requiring dose reduction and/or discontinuation of nintedanib in patients with idiopathic pulmonary fibrosis. Objectives: The objectives of this study were to clarify the incidence of dose reduction and/or discontinuation following the commercialization of nintedanib and to investigate predictors of dose reduction and/or discontinuation of nintedanib at our hospital. Methods: We retrospectively identified 25 patients who had received nintedanib 150 mg twice daily at Sendai Kousei Hospital and categorized them into two groups according to whether they had or had not required dose reduction and/or discontinuation and sought to identify predictors of dose reduction and/or discontinuation. Results: Seventeen patients developed adverse events, which included diarrhea (n=10, 44%), hepatotoxicity (n=7, 28%), and anorexia (n=2, 16%). No adverse event-related deaths occurred during the study period. Patients who required dose reduction and/or discontinuation were significantly older than those who did not (72 years vs 67 years; P=0.047). Body surface area (BSA) was significantly lower in the group that needed dose reduction and/or discontinuation than in the group that did not (1.63 m2 vs. 1.78 m2; P=0.028). Multivariate logistic regression revealed that the association of low BSA with dose reduction and/or discontinuation was statistically significant. Conclusions: A low BSA was associated with dose reduction and/or discontinuation of nintedanib in patients with idiopathic pulmonary fibrosis. Further studies in larger patient samples are needed to validate these findings.